Pemanfaatan Marketplace Shopee Sebagai Solusi Pemasaran Digital Bagi Generasi Z di Pedesaan - Nurdin, Ibnu Phonna; Miska Raihani, Wilda; Putri, Annisah; Yulianda, Riki; Keumalawati, Cut; Handayani, Gusti; Kusdiane, Susvia Delta; Asri, Muh.; Mustaqim (Yayasan Inspirasi El Burhani, 2025)
Introduction: The development of digital technology has opened up new opportunities in online marketing through E Commerce. This provides benefits for all people who want to market their products through the marketplace, especially for Generation Z in rural areas. Objective: This service program aims to provide education for Generation Z in rural areas so that they are able to expand their marketing network through the Shopee application. Method: This activity is carried out online so that all Generation Z in rural areas in various regions can participate in this activity. This service activity consists of 4 activities, namely: 1. Introduction to the Shopee application as a marketplace, 2. Creating a shop at Shopee, 3. Strategies for increasing sales at Shopee, and 4. Order and delivery management. Result: The results of the activity showed that after the education was carried out, Generation Z understood and understood the concept and Shopee application used. In addition, the participants also actively listened and asked questions related to the material that they did not understand. Conclusion: Therefore, it can be concluded that this service has a positive impact on Generation Z in rural areas. The role of the relevant government is needed to ensure the sustainability of this online marketing. Some of the things needed are related to funding and facilities for Generation Z business actors in rural areas